MPD: Introduction of a single player prisoner's dilemma application for medical experiments. (April 2022) - Mantas, Vasileios; Pehlivanidis, Artemios; Papanikolaou, Katerina; Papageorgiou, Charalambos
HIghlights: There is no shared validated tool for prisoner's dilemma tasks in medical literature. We have developed an open source application for single player PD tasks able to simulate a large number of single player prisoner's dilemma versions. Portability and customizability. Assist future researchers in designing their PD version and contribute to increasing methodologies' credibility and mitigating cross-validation discrepancies. Abstract: Background: Prisoner's dilemma is one of the most popular concepts among scientific literature. In medical literature the majority of prisoner's dilemma experiments with human participants implement computerized means. Despite this, there is no shared validated tool for prisoner's dilemma tasks. Methods: The application is developed in Javascript programming language and makes use of the pixijs library for WebGL rendering. To create a custom trial, a set of variables have to be set. These refer to the linguistics, user controls, available choices, computer strategy, interaction flow (simultaneous or sequential), opponent's choice prediction requirement, noise induction, human opponent behavior simulation, the way resulted data will be handled and more. Results are in JSON format and include time interval data. Results: We have developed an application which, given the various parameters experimenter can modify, is able to simulate a large number of single player prisoner's dilemma versions. It is open source with no installation requirement, executable by any modern internet browser remotely or locally with the ability to post data results either locally or remotely. Experimenter only has to modify certain starting values in order to create his design of choice. Two examples are included, with initial settings and results, to demonstrate the use and validity of the application. Conclusions: Our aim is to assist future researchers in their methodological designs. In this scope, our application, has the minimum requirements, can be served either locally or remotely, has a wide range of modifiable parameters and takes care of the resulted data. In the long term, a shared and validated tool would contribute to increasing methodologies' credibility and mitigating cross-validation discrepancies.